Say No To Drugs & Stop Bullying - Firmansyah, Hery; Marbun, Jessica; Marshanda, Talitha; Michelle, Grace Bernadette; Gunawan, Angelene Vivian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Narcotics abuse cases in Indonesia are increasing every year. The danger of narcotics lurking the next generation of young people, namely children in school and also many other people who abuse them. The lack of legal and social knowledge and awareness about narcotics causes people, especially teenagers, to feel curious about trying drugs. Article 104 of the Narcotics Law, emphasizes that the public has the widest opportunity to participate in and assist in the prevention and eradication of drug dependence and illicit trafficking. Besides Narcotics, another thing that is rife in the school environment is bullying. Children as perpetrators of bullying cannot be separated from the threat of punishment. According to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, children can be subject to action sanctions and criminal sanctions, both main and additional crimes. If a child who is in conflict with the law is sentenced to imprisonment, then the prison sentence that can be imposed is ½ (half) of the maximum sentence of imprisonment for an adult. Thus, children who violate criminal provisions can be prosecuted by law. The output produced through Community Service aims to increase legal and social youth's knowledge and awareness of the dangers of using Narcotics and the legal consequences of bullying. Kasus penyalahgunaan narkotika di Indonesia semakin marak di setiap tahunnya. Bahaya narkotika tidak lepas mengintai generasi muda penerus bangsa yaitu anak-anak di bangku sekolah hingga banyak masyarakat yang menyalahgunakan. Kurangnya pengetahuan serta kesadaran hukum dan sosial akan bahaya narkotika menyebabkan masyarakat terutama di kalangan remaja termakan rasa penasaran ingin mencoba. Pasal 104 Undang-Undang Narkotika, menegaskan bahwa masyarakat memiliki peluang sebesar-besarnya untuk berpartisipasi dan membantu mencegah dan memberantas ketergantungan dan peredaran gelap Narkoba. Selain narkotika, hal yang marak terjadi dalam lingkungan sekolah adalah bullying atau perisakan. Anak sebagai pelaku bullying tidak lepas dari ancaman pidana. Anak dalam Undang Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak dapat dikenakan sanksi tindakan dan sanksi pidana baik pidana pokok atau tambahan. Untuk anak yang berkonflik dengan hukum maka maksimum ancaman hukuman tindak pidananya dikurangi 1⁄2 (setengah) dari maksimum ancaman hukuman yang dikenakan pada orang dewasa. Demikian, anak yang melanggar ketentuan pidana tidak lepas dari jerat hukum. Luaran yang dihasilkan melalui Pengabdian Kepada Masyarakat yang telah dilaksanakan adalah untuk meningkatkan pemahaman hukum dan sosial generasi muda akan bahaya penggunaan narkotika dan akibat hukum anak pelaku bullying.